Attribution Theory: How is it Used? - Eric D. Rubenstein; Andrew C. Thoron (EDIS)
Attribution theory is defined as the way that individuals envision the success or failure of their own behavior or the behavior of others. This 4-page fact sheet explains how instructors, whether formal or informal, can use this theory in their learning environment to enhance their learners’ knowledge and comprehension. Written by Eric D. Rubenstein and Andrew C. Thoron, and published by the UF Department of Agricultural Education and Communication, September 2014.